Experimental behavior of laser cut I-beam-to-CHS-column steel-concrete composite joints under vertical loads. (June 2021) - Piscini, Andrea; Morelli, Francesco; Salvatore, Walter
Abstract: This paper presents the results of an extensive experimental campaign on I beam to Circular Hollow Section column joints obtained cutting a dedicated slot on the column through precision laser technology and letting the beam or connection plates pass through the column itself. The application of this technology minimizes the welding necessary to complete the connection, the number and dimensions of the plates, and it assures the continuity of the beam within the column leading to a more favorable mechanical behavior of the joint under vertical loads. Even if the passing-through beam idea was already tested in the past, only recently the laser cutting technology made it really feasible and competitive from a technical and economic point of view. However, several issues about this structural solution needs further clarifications, especially when considering the interaction of the bare steel node with the reinforced concrete slab or the influence of the infill concrete in the column. For this reason, within this research, different joint configurations were designed extrapolating them from realistic case study buildings and testing them under monotonic vertical loads. To deeply understand their behavior, the specimens were designed and realized as four-way joint, differentiating the structural scheme of the joint connecting the main beams and the joints connecting the secondary beams, obtaining a representation of the most common solutions currently adopted in the real practice. Graphical abstract: Unlabelled Image Highlights: Laser cutting allows the efficient realization of 4-way beam-to-column joints. Beams passing through the column optimize the joint behavior under vertical loads. Infill concrete impedes the buckling of the passing-though plates inside the column.